Teaching In Learning Style Strategies Of Se-Cond Language Acquisition (SLA) Learners - Muhammad Rusdi; Agussalim Agussalim; Hardiyan Hardiyan; Ibrahim Manda; Sam Hermansyah (La Ogi : English Language Journal, 2022)
The purpose of this study is to determine how the level of learners learning style strategies and what types of learning style strategies are dominantly chosen by learners during the learning process. In addition, this study aims to determine whether the learning style strategies applied by teachers in the learning process affect students’ understanding abilities.This research used qualitative research methods. The population of this study were students of eighth grade students MTs. Ibrahim Uluale Sidrap of the period 2020-2021. The total population is 87 students consisting of four classes. Class VIII.A was taken as a sample, with a total sample of 22 students. The in-strument used in this study was a closed questionnaire.The result of this research indicate that at the level of learning style strate-gies, students are able to understand the material presented if the teachers uses more than one type of learning strategy. And in the case of this study, students are more dominant in choosing the type of kinesthetics learning style strategy. Based on the result of the questionnaire data, there 16 students (74%) strongly agree that the learning strategies applied in the learning process affect students’ understand-ing. Of the four types of learning strategies, the types kinesthetics learning strate-gy is a learning strategy that helps understanding in the learning process.